2018
DOI: 10.1080/07347332.2018.1471564
|View full text |Cite
|
Sign up to set email alerts
|

Unique associations of eudaimonic and hedonic wellbeing with psychosocial adjustment in breast cancer survivors

Abstract: Purpose: Eudaimonic wellbeing (e.g., meaning, purpose in life) and hedonic wellbeing (e.g., happiness, life satisfaction) are related but conceptually-distinct facets of wellbeing. Eudaimonic wellbeing is highly underexplored in cancer research despite its relevance to important existential concerns faced by cancer survivors. Therefore, this study examined the unique associations of eudaimonic and hedonic wellbeing with adjustment in breast cancer survivors. Methods: Women diagnosed with early-stage breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Evidence supports its protective role against a number of diseases, disabilities, and early mortality through the optimal regulation of physiological and neurological systems (Ryff, 2013(Ryff, , 2014 and gene expression (Fredrickson et al, 2015). In addition, research has reported that eudaimonic wellbeing is associated with greater post-traumatic growth in breast cancer survivors (Moreno et al, 2018), that it protects against the health challenges ensuing from aging (Ryff, 2013) and has been linked to successful aging (Boccardi and Boccardi, 2019;Hill and Turiano 2014). Research has also reported that high eudaimonic well-being in older people is related to a reduced risk of death (Steptoe et al, 2015) and of frailty (Andrew et al, 2012), while having a greater purpose in life is associated with a reduced risk of stroke (Kim et al, 2013), of cardiovascular events (Cohen et al, 2016), and of developing Alzheimer's disease and mild cognitive impairment in older people (Boyle et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Evidence supports its protective role against a number of diseases, disabilities, and early mortality through the optimal regulation of physiological and neurological systems (Ryff, 2013(Ryff, , 2014 and gene expression (Fredrickson et al, 2015). In addition, research has reported that eudaimonic wellbeing is associated with greater post-traumatic growth in breast cancer survivors (Moreno et al, 2018), that it protects against the health challenges ensuing from aging (Ryff, 2013) and has been linked to successful aging (Boccardi and Boccardi, 2019;Hill and Turiano 2014). Research has also reported that high eudaimonic well-being in older people is related to a reduced risk of death (Steptoe et al, 2015) and of frailty (Andrew et al, 2012), while having a greater purpose in life is associated with a reduced risk of stroke (Kim et al, 2013), of cardiovascular events (Cohen et al, 2016), and of developing Alzheimer's disease and mild cognitive impairment in older people (Boyle et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, resignation-acceptance coping can lead to the sense of losing control over disease and then more depressive symptoms in patients with cancer 11 . Moreover, the negative relationship between depressive symptoms and life satisfaction has been confirmed in previous studies 24–26 . The literature and theories showed that self-care self-efficacy, coping strategies, and depressive symptoms play a mediating role in the relationship between social support and life satisfaction.…”
mentioning
confidence: 84%
“…These features could challenge the core assumptions that individuals hold about their value, their relationship with others, and their future, adversely affecting life satisfaction. [24][25][26] In summary, although social support, self-care self-efficacy, coping strategies, and negative emotions are associated with life satisfaction, these variables are not independent of each other, and the interaction between these variables should be considered in clinical psychological intervention. In this case, supportive care interventions might be enhanced by addressing the impact of social support on self-care self-efficacy, coping strategies, and depressive symptoms.…”
Section: Et Almentioning
confidence: 99%
“…Understandably, many existing psychosocial interventions are designed to help breast cancer survivors cope with adverse cancerrelated sequelae (Matthews et al, 2017), consistent with the broader literature on psychosocial interventions for cancer patients and survivors (Kalter et al, 2018;Sanjida et al, 2018;Stanton, 2006). Less attention has been paid to enhancing well-being in this population, despite evidence linking well-being to better health-related outcomes (Chida & Steptoe, 2008;Hernandez et al, 2018;Moreno et al, 2018). Indeed, enhancement of positive psychological processes may be equally, if not more important, for health than reducing distress (e.g., Chida & Steptoe, 2008;Craske et al, 2019;Moreno et al, 2018).…”
mentioning
confidence: 89%
“…Less attention has been paid to enhancing well-being in this population, despite evidence linking well-being to better health-related outcomes (Chida & Steptoe, 2008;Hernandez et al, 2018;Moreno et al, 2018). Indeed, enhancement of positive psychological processes may be equally, if not more important, for health than reducing distress (e.g., Chida & Steptoe, 2008;Craske et al, 2019;Moreno et al, 2018). To date, there is a lack of understanding about the factors that promote well-being among breast cancer survivors, and, within this population, few interventions have been designed to target these processes.…”
mentioning
confidence: 99%